Pengaruh Pengungkapan Terkait Keberlanjutan dan Risiko Iklim Terhadap Nilai Perusahaan - Febri Dwi Rohmatun; Christina Dwi Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the impact of sustainability and climate risk disclosure on firm value in climate-sensitive sectors listed on the Indonesia Stock Exchange. The study is relevant given the increasing attention of investors and regulators to sustainability transparency, particularly following the issuance of the International Financial Reporting Standards (IFRS) Sustainability Disclosure Standards IFRS S1 and IFRS S2. These standards emphasize sustainability and climate-related disclosures through four main pillars, namely governance (GOV), strategy (STR), risk management (RIS), and metrics and targets (MET), which are considered financially material in influencing firm value. The 2023–2024 period is considered relevant as it reflects the early phase of adoption and adjustment to IFRS S1 and IFRS S2-based disclosures in Indonesia. This study employs a quantitative approach using multiple linear regression analysis. The research sample was selected using a purposive sampling method and consists of climate-sensitive companies with a total of 408 observations. The data used were secondary data obtained from companies’ annual reports and sustainability reports. Firm value is measured using Price to Book Value (PBV), with control variables including firm size, profitability, leverage, and firm age. The results show that strategy disclosure has a positive and significant effect on firm value, while risk management and metrics and targets disclosures have a significant negative effect. Meanwhile, governance disclosure does not have a significant effect on firm value. This study concludes that market responses to sustainability and climate risk disclosures are heterogeneous.